Analisis Yuridis Terhadap Putusan Yang Mengabulkan Gugatan Perceraian Disebabkan Konflik Suami dan Istri (Studi Putusan Nomor 2612/Pdt.G/2017/Pa.Bks). - -, Umayah; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
The purpose of this study was to find out the legal basis for divorce due to husband and wifeconflict and to find out the judge’s consideration in granting a divorce suit in case Number 2612 /Pdt.G / 2017 / PA.Bks). This research is library research with a normative juridical approach, usingthe descriptive analysis method. The results of this study are that due to the dispute, Plaintiff feelsuncomfortable in his household relationship with Defendant. Therefore, judges realize legal protectionfor Indonesian citizens, especially women, namely in Law Number 23 of 2004 Article 1 Paragraph (1),Compilation of Islamic Law Article 132 Paragraph (1) and Government Regulation of the Republic ofIndonesia Number 7 of 1975 Article 20 Paragraph (1) concerning the implementation of Law Number7 of 1974 concerning Marriage. From the findings data, it is analyzed that the judge’s decision ingranting the lawsuit is because the lawsuit submitted has met the formal and material requirements aswell as the facts that were revealed in the trial.